Examining instruction, achievement, and equity with NAEP mathematics data. - Lubienski, Sarah Theule (Education Policy Analysis Archives, 2006)
The purpose of this article is two-fold. First, it reports on a study of the distribution of reform-oriented instructional practices among Black, White and Hispanic students, and the relationship between those practices and student achievement. The study identified many similarities in instruction across student groups, but there were some differences, such as Black and Hispanic students being assessed with multiple-choice tests significantly more often than were White students. Using hierarchical linear modeling, this study identified several significant positive—and no negative—relationships between reform-oriented practices and 4th-grade student achievement. Specifically, teacher emphasis on non-number mathematics strands, collaborative problem solving, and teacher knowledge of the NCTM Standards were positive predictors of achievement. An analysis of interaction effects indicated that the relationships between various instructional practices and achievement were roughly similar for White, Black and Hispanic students. The second purpose of this article is to make comparisons with another study that used the same NAEP data, but drew very different conclusions about the potential for particular instructional practices to alleviate inequities. A study published in EPAA by Wenglinsky (2004) concluded that school personnel can eliminate race-related gaps within their schools by changing their instructional practices. Similarities and differences between these two studies are discussed to illuminate how a researcher's framing, methods, and interpretations can heavily influence a study's conclusions. Ultimately, this article argues that the primary conclusion of Wenglinsky's study is unwarranted. Keywords: equity, hierarchical linear modeling; mathematics achievement; mathematics instruction; NAEP.